Mechanical performance analysis of a dual-spar floating wind farm considering different shared mooring systems - Xiang Lin; Jingrui Zhao; Wenzhou Liang; Zhishuai Liu; Zihang Yu (Frontiers in Marine Science, 2025)
Introduction In recent years, as floating wind turbines advance into deeper waters, mooring systems represent a growing share of the overall investment. Shared mooring can simplify mooring arrangements and improve the economic efficiency of wind farms. However, it also increases the dynamic complexity of multi-turbine systems, introducing risks of high tension levels and snap events under extreme conditions, which must be addressed during the mooring design phase. Methods This study compares the coupled dynamic responses of three typical shared mooring systems: pure steel cable, polyester rope with a clump weight, and chain with a buoy. Mooring design is based on the catenary equation, and time-domain simulations are conducted using OrcaFlex to analyze the impact of various shared mooring configurations on the hydrodynamics and mooring performance of wind turbine systems. Results The results show that, compared to the baseline configuration, the taut single-weighted configuration is more effective in reducing the fluctuation of mooring tension under extreme conditions, thus avoiding the occurrence of snap events. As the clump weight mass increases, the surge motion of the platform is effectively suppressed, but the heave and pitch motions may become more pronounced. Therefore, a balance must be struck between the clump weight mass, platform motion, and mooring tension to achieve optimal overall performance. The catenary with buoy configuration shows similar results to the taut single-weighted configuration; however, the maximum tension of shared mooring may occur at the buoy connection. Additionally, excessive net buoyancy can exacerbate the dynamic characteristics of the buoy and raise the risk of collision between the buoy and passing vessels. This study contributes to a deeper understanding of shared mooring systems and provides valuable guidance for their design.